The inclusion of deaf in the professional e technological education: glossary in libras for the civil constructions area (Research, Society and Development, 2020)
This article describes the creation of a bilingual glossary, Portuguese Language (LP) and Brazilian Sign Language (LIBRAS), of metallic construction components as didactic material for students with hearing impairment. The investigation aimed to include Deaf students in Professional and Technological Education (EPT). For this, the reseach was developed on a campus of the Federal Institute of Minas Gerais (IFMG), based on a demand during the Construction Technology classes, since the vocabulary of the content is non-existent in the form of a LIBRAS glossary based on pratical classes and investigation of the elements that make up drywall and steel frame models. The final product obtained was a glossary with the technical terms of civil construction using videos explaining each element studied. Didactic material is expected to be used in other educational contexts.